A global quality control system to check PT‐INR portable monitor for Antivitamin K antagonists. (15th April 2014) - Testa, S.; Paoletti, O.; Bassi, L.; Dellanoce, C.; Morandini, R.; Lippi, G.
Summary Introduction Although most guidelines for quality assessment of INR PMs recommend specific procedures, no clear regulation or methodology is required for outpatients in our country. We have developed a specific INR portable monitor (PM) quality control system within our telemedicine organization to check over time quality performances and plan corrective actions. Methods Based on current guidelines for laboratory QC, the following aspects were assessed: suitability of PM, defined in terms of imprecision and accuracy; intra‐assay imprecision, defined according to monthly revision of Levey–Jennings cards with data from each peripheral healthcare unit (PHU), using an internal QC provided by the manufacturer (CV ± 20% considered as acceptable); quarterly accuracy study, for assessing agreement between analytical instruments, based on duplicate analysis of three samples with INR values reflecting different therapeutic ranges (differences ± 0.5 considered as acceptable); external quality assessment (NEQAS). Results In the nine PHU, 18 portable monitors were used to perform 22 929 test during year 2010. Analytical imprecision was low, showing CVs always <5%. Accuracy check showed two of 216 results out of range (0.92%), thus providing timely indication for instrument replacement. The external QC NEQAS showed optimal performance. Conclusion The current protocol for INR PMs quality assessment was effective to establish and maintain a reliable control of devices, ensuring the quality of analytical data over time. National authorities should be prompted to guarantee and apply correct protocols for INR‐PM use.